The Influence of Sustainable Investment on Guizhou SME Performance Based on ESG Standards - Chengwei Wen (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the connection between Environmental, Social, and Governance (ESG) factors that can impact a company's financial and operational performance. The research looks at how stakeholder and legitimacy theories can help explain the effects of the variables used in the study. Additionally, the study makes a unique contribution to the existing research on ESG and performance by examining the link between ESG and firm performance over ten years. Furthermore, the study explores the relationship between ESG and operational performance in SMEs in Guizhou. This provides valuable insights into how ESG can impact the performance of SMEs. ESG provides a comprehensive framework for businesses and investors to address environmental, social, and corporate governance issues. It promotes integrating economic and social benefits for sustainable corporate management and financial investment development. The number of respondents for this study was 380 enterprises from Guizhou. The results of this study show that parents’ purchase intention on training courses for their children would be impacted by their transformational leadership, organizational innovation, and social capital.